Sex Ratio, Age Structure and Parasitism in Unaspis mabilis (Hemiptera: Diaspididae) in the Philippines - Joeseph S. Quisado; Joel P. Limson; Darlyn B. Posas; Bryan V. Novio; Celia dR. Medina; Luis Rey I. Velasco (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Lanzones scale insect (LSI) has been an important insect pest of lanzones since its first record in 2004. It causes massive defoliation on trees which eventually results to underdeveloped and sour fruits. Different lanzones-growing areas in the Philippines were surveyed for LSI along with its associated parasitoids in commercial lanzones farms located in Laguna (Los BaÃ±os,Nagcarlan and Sta. Maria), Oriental Mindoro (Villa Cerveza, Villa Cerveza, San Gabriel-Alcate), Negros (Abante-Pamplona, Poblacion - Pamplona,Â Lunga, Valencia, Talisay - Negros Occidental, Jawa-Valencia, Lunga-Valencia, Bongbong), Misamis Occidental (Aloran - Misamis Occidental, Calamba, Oroquieta, Sapang Dalaga, Plaridel), Camiguin (Catarman, Poblacion, Sagay, Tagdo, Mahinog), North Cotabato (Makilala, Kidapawan, and Kabacan) and Sulu (Maimbung, Patikol,Talipao).Â From each collection site, a total of 10 infested trees were sampled at random with leaflets (N=10) collected in four cardinal directions around canopy. Leaflets were scanned, photographed, and transported to the laboratory. Population estimates of each local population was obtained along with demographic structure viz. age structure and male-female sex ratio. The sample per tree were kept individually in customized cages for parasitoid emergence and determination of parasitization rate. Parasitoids were identified as Aphytis sp., Encarsia sp. and 2 other unidentified species. LSI population and percent parasitism in Laguna were quite high compared to North Cotabato. Results of this study will contribute to the basic knowledge needed to improve control strategy on LSI.